An introduction to scientific research methods in geography - Montello, Daniel R. 1959- (SAGE, 2006)
Explaining the key elements of scientific philosophy and basic research concepts, this text discusses all parts of the research process, including generating research ideas, data analysis and the use of geographic information techniques.